Modeling study of the heat of absorption and solid precipitation for CO2 capture by chilled ammonia. Issue 35 (27th June 2019) - Zhou, Qiang; Liu, Lan; Croiset, Eric; Tan, Zhongchao; Liu, Qingcai; Yang, Jian
Abstract : Prediction of (a) solution speciation change and (b) heat of CO2 absorption in the chilled ammonia process (CAP). Abstract : The contribution of individual reactions to the overall heat of CO2 absorption, as well as conditions for solid NH4 HCO3 (s) formation in a chilled ammonia process (CAP) were studied using Aspen Plus at temperatures between 2 and 40 °C. The overall heat of absorption in the CAP first decreased and then increased with increasing CO2 loading. The increase in overall heat of absorption at high CO2 loading was found to be caused mostly by the prominent heat release from the formation of NH4 HCO3 (s). It was found that NH4 HCO3 (s) precipitation was promoted for conditions of CO2 loading above 0.7 mol CO2 /mol NH3 and temperatures less than 20 °C, which at the same time can dramatically increase the heat of CO2 absorption. As such, the CO2 loading is recommended to be around 0.6–0.7 mol CO2 /mol NH3 at temperatures below 20 °C, so that the overall absorption heat is at a low state (less than 60 kJ mol −1 CO2 ). It was also found that the overall heat of CO2 absorption did not change much with temperature when CO2 loading was less than 0.5 mol CO2 /mol NH3, while, when the CO2 loading exceeded 0.7 mol CO2 /mol NH3, the heat of absorption increased with decreasing temperature.